2020
DOI: 10.4025/actasciagron.v42i1.42490
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters and path analysis of crambe: An important oil plant for biofuel production

Abstract: Crambe is an oilseed plant producing oil that can be used for various industrial purposes, including the production of biofuel. It is a short-cycle, non-food plant that can be grown as a second crop following soybean or corn crops and using the same agricultural machinery. This work aimed to estimate genetic parameters and correlations between traits of genotypes grown for two years in seven locations in two Brazilian states. The cultivar FMS Brilhante and the lines CR 1101, CR 1102, CR 1105, CR 1202, CR 1303,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, the correlation coefficient only measured the linear relationships, while nonlinear variables could still be valid. A high correlation does not imply a direct cause-and-effect relationship between the analyzed variables [ 35 ]. According to the results obtained in the GGE Biplot analysis the direct effect magnitudes can change based on the growth environment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the correlation coefficient only measured the linear relationships, while nonlinear variables could still be valid. A high correlation does not imply a direct cause-and-effect relationship between the analyzed variables [ 35 ]. According to the results obtained in the GGE Biplot analysis the direct effect magnitudes can change based on the growth environment.…”
Section: Resultsmentioning
confidence: 99%
“…When assessing quality parameters of eight acerola genotypes, Mariano-Nasser et al (2017) found low CV e values (3.0-7.9%) for skin lightness, soluble solids, titratable acidity and ascorbic acid and medium CV e values (13.8-19.9%) for skin chroma and hue. Furthermore, the relative CV (CV g /CV e ) was higher than 1 for all quality traits, which is recommended for genotype selection (Azevedo et al, 2021;Vasconcelos et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The estimates of genetic parameters found in this study indicate similar results for different approaches (Bayesian × classical methods), which agrees with studies on kale (Brito et al, 2019) and physic nut (Jatropha curcas L.) (Evangelista et al, 2022). Some advantages of Bayesian inference in relation to frequentist determination of variance components (and consequently coefficients of repeatability) include the feasibility of using previous data information (priori), the lower sensitivity to outliers and lower data assumptions, such as experimental balance and high sample size (Singh, L-Yassin, & Omer, 2015), resulting in more accurate estimates of variance, as reported in guava (Silva et al, 2020) and soybean (Volpato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%